The Role of Moral Education in Madrasah Ibtidaiyah: Building an Attitude of Respect and Love for Children towards Parents - Amanda Sofian; Nur Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to examine the role of moral education in madrasah ibtidaiyah in building children's attitudes of respect and affection towards their parents. Using qualitative descriptive methods, this research was conducted at Madrasah Ibtidaiyah Bima Regency in the even semester of the 2023/2024 academic year. Data was collected through observation, interviews and documentation involving school principals, teachers, students and parents. The results of the research show that moral education at madrasah ibtidaiyah has a significant positive impact on the formation of children's personalities, especially on the development of attitudes of respect and affection towards parents. Effective methods include teacher example, good behavior habits and integration of moral values ​​in daily learning. Cooperation between schools and parents is also considered a key factor in strengthening moral education. This research concludes that moral education at madrasah ibtidaiyah not only produces individuals with good morals but also contributes to the formation of a more harmonious society.